Kabir Azabıyla İlişkilendirilen Âyetlerin Tahlil ve Değerlendirilmesi - (:unkn) unknown (My University, 2016)
Kabir azabının varlığı tarih boyunca az da olsa tartışılmış olup bugün de zaman zaman gündeme gelmektedir. Kur'ân-ı Kerim'de kabir azabıyla ilgisi kurulan âyetlerin delâletleri hususunda ihtilaf edilmiştir. Bu makalede bu âyetlerin ne manaya geldiği ilk dönem tefsirlerinden başlayıp günümüze kadar gelen öne çıkmış tefsirler ışığında tahlil edilmiş ve değerlendirilmiştir.

The presence of the punishment of the grave, although little, has been discussed throughout the history and it also comes up today from time to time. The verses associated with the punishment of the grave have been disputed in regards to their meaning. In this article, the meanings of these verses have been analyzed and evaluated in the light of leading commentaries, starting from the first period to the present day.
Analysis and Evaluation of the Verses Associated with the Punishment of the Grave
Keywords: Din Bilimi